Artikel Pemanfaatan Lidah Mertua Sebagai Hair Tonic Untuk Perawatan Rambut Rontok - aprilia aprilia aprilia (JURNAL PENDIDIKAN DAN KELUARGA, 2018)
Hair is said to fall out if it reaches 50-100 strands. This research aims to analyze the use of senseviera as hair tonic for the treatment of hair loss .This research is a quasi-experiment with the design of Non Equivalent Control Group Design. The population is women aged 19-25 years who use hijab. The sampling technique was carried out by purposive sampling technique conducted voluntarily as many as 9 people. After obtaining the data, the normality test, homogeneity test and variance analysis test (ANAVA) were first carried out and continued with the duncan test.The results of the analysis showed that there was no change in the control group (X1) with an average value of 2.33 (pretest) to 2.73 (posttest). For the experimental group 1 frequency of 2 times a day (X2) since the first treatment (pretest) can be seen changes with an average of 2.00 (pretest) to 3, 33 (posttest). Whereas in the experimental group 2 frequency 1 time 3 days (X3) also changed since and get an average of 2.00 (pretest) to 3.07 (posttest). The average calculation of the three treatment groups stated that Fcount> Ftable (5,810> 1,860), which means that there was a significant.